Pineapple Growing in the Florida Home Landscape - Jonathan H. Crane (EDIS)
Revised! HS-7, a 9-page fact sheet by Jonathan H. Crane, provides homeowners with an expanded and reorganized basic reference for growing pineapple in the home landscape. Tables include information on cultural practices by month, fertilizer program, pulp characteristics, and nutritional values. Included in the Master Gardener Handbook. Published by the UF Horticultural Sciences Department, October 2005.